Pengaruh Lingkungan Kerja, Keselamatan Kesehatan Kerja, dan Beban Kerja terhadap Produktivitas Kerja Karyawan di UD. Amanah - Sari, Selvira Ayu Nur Chintya; Nersiwad, Nersiwad; Kasnowo, Kasnowo (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to examine the effects of the work environment, Occupational Safety and Health (OSH), and workload on employee productivity levels at UD. Amanah. A quantitative associative approach was used, involving the distribution of questionnaires to 60 permanent employees in the production department. Data processing began with descriptive statistical analysis, validity testing, and reliability testing. After meeting all the requirements of the classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation, and linearity), the analysis continued with multiple linear regression, t-tests, F-tests, and R² analysis. Field findings confirm that work environment conditions and the implementation of occupational safety and health (OSH) have a positive and significant effect on productivity (t = 9.094 and t = 8.497; sig. = 0.000). On the other hand, workload has a significant negative effect (t = -4.727; sig. = 0.000). Collectively, these three factors account for 77.9% of the variation in productivity (F = 65.778; sig. = 0.000), while the remainder is explained by other variables..